Feminist Analysist of Make-Up Incentive Policy to Women Police Officer in Indonesia - Orisa Shinta Haryani (Yayasan Jurnal Perempuan, 2017)
Police institution is one of the institutions adopting a strong patriarchal culture. Indonesian National Police (Polri) is doing many jobs to accommodate public demand in relation to the women participation in Polri and to create an institution that issues gender-friendly policies. Many efforts have been done by Polri such as increasing the recruitment quota for policewoman (Polwan) and issuing a policy permitting Polwan to wear hijab. However, there is an interesting policy that relates to Polwan, namely Make-up allowance provided only for Polwan. The provision of Make-up allowance shows that the Polwan is forced to look pretty by wearing make-up. It raises a question on how the role of Polwan in Polri institution is. Even though the recruitment number of Polwan in Polri has been increased but in reality, Polwan is still places in domestic sphere. This is indeed not according to the objective of Polri as a genderfriendlyinstitution especially for women. This is a qualitative research by using the concept of beauty of myth and objectification and comodification concept in analyzing the problem.